Microstructure and physical performance of laser-induction nanocrystals modified high-entropy alloy composites on titanium alloy. (5th March 2017) - Li, Jianing; Craeghs, Werner; Jing, Cainian; Gong, Shuili; Shan, Feihu
Abstract: Ultrafine nanocrystals (UNs) modified high-entropy alloy composites (HEACs) were fabricated by laser-melted deposition (LMD) of the yttria partially stabilized ZrO2 (YPSZ) and the FeCoCrAlCu mixed powders on the aviation turbine blade made of the additive manufacturing (AM) TC17 titanium alloy. Such HEACs exhibited the finer microstructure free of micro-crack under an action of YPSZ, also relative stable atomic group of UNs owned the short-range order was produced attached to such HEACs matrix. Formation mechanisms of the AlCu2 Zr UNs, amorphous and the nanoscale icosahedral quasicrystals (I-phase) with five-fold symmetry in HEACs were explored extensively by mean of the high resolution transmission electron microscope (HRTEM); also, under the actions of these various phases, such laser-induction HEACs exhibited the better wear performance than that of the FeCoCrAlCu LMD high-entropy alloy. With SiB2 addition, lots of the one-dimensional nanostructure materials (nanorods) were produced, retained UNs can be easily reunited due to a surface effect, retarding growth of nanorods in a certain extent. This research may provide the essential theoretical and experimental basis to improve the quality of the laser 3D print composites. Graphical abstract: Highlights: Ultrafine nanocrystals modified high-entropy alloy composites (HEACs) were fabricated. With YPSZ addition, the HEACs exhibited the finer microstructure free of the micro-crack. Relative stable atomic group of UNs owned short-range order was produced. Nanoscale icosahedral quasicrystals with five-fold symmetry are obtained in HEACs. With SiB2 addition, lots of one-dimensional nanostructure materials were produced.